SOCIAL WORK TECHNOLOGIES IN INCLUSIVE ENVIRONMENT OF HIGHER EDUCATIONAL INSTITUTIONS OF UKRAINE - Popovych, Vasyl; Hordienko, Nataliia; Kuzmin, Viktor; Taran, Volodymyr; Pushchyna, Iryna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The modern educational environment is oriented towards satisfying the needs of all education seekers, and such group of children as orphans, including the orphans graduated from the residential educational establishments, requires such conditions that provide them successfully to undergo the adaptive period during the first year of study at the higher educational institutions.